THE EFFECT OF THE TGT-TYPE COOPERATIVE MODEL ASSISTED BY QUESTION CARD MEDIA ON THE MOTIVATION AND LEARNING OUTCOMES OF MAETHMATICS OF GRADE IV ELEMENTARY SCHOOL GROUP IV BEBANDEM DISTRICT - I Made Sudarma; I Made Sedana; Ni Nyoman Lisna Handayani (SOSIOEDUKASI, 2025)
This study aims to determine the magnitude of the influence of the Cooperative Type Teams Games Tournament (TGT) Assisted by Question Card Media on Student Learning Motivation and Mathematics Learning Outcomes. The study population was all fourth-grade elementary school students in Cluster IV, Bebandem District. The sample was determined by group random sampling technique. The sample in this study amounted to 43 people. Learning outcome data used a multiple-choice test consisting of 20 questions, student learning motivation was collected through a questionnaire. Data were analyzed using MANOVA (multivariate Analysis of Variance). The results of the study showed that: First, there was a significant difference in Mathematics learning motivation between students who studied with the Cooperative Learning Model TGT Type Assisted by Question Card Media and students who studied with conventional learning models in fourth-grade elementary school students. Second, there was a significant difference in learning outcomes between students who studied with the Cooperative Model TGT Type Assisted by Question Card Media and conventional learning models in fourth-grade elementary school students. Third, Simultaneously, there is a significant difference in learning motivation and learning outcomes in Mathematics between students who learn with the TGT Type Cooperative Learning Model Assisted by Question Card Media and students who learn with the conventional learning model in grade IV of elementary school students. The conclusion is that there is an influence of the TGT model assisted by question card media on student motivation and learning outcomes.